2018
DOI: 10.1111/1556-4029.13968
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cutting Agents in Drug‐Positive Seized Exhibits within the United States

Abstract: The following report summarizes a study performed on seized drug exhibits collected in two U.S. states to evaluate the presence and identification of cutting agents. Aliquots of seized drug materials from Kentucky (n = 200) and Vermont (n = 315) were prepared using a dilute‐and‐shoot procedure. Initial analysis was performed using gas chromatography–mass spectrometry (GC‐MS) followed by analysis using liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐QTOF). Active compounds detected overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 62 publications
(96 reference statements)
1
67
0
Order By: Relevance
“…The addition of diluents (or “cutting agents”) is common practice when preparing illicit drugs, with most samples containing the cutting agent in vast excess to the active component. This presents a significant analytical challenge, since diluents may be fluorescent or Raman active, so interference, suppression, or obscuration during regular Raman analysis can occur [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of diluents (or “cutting agents”) is common practice when preparing illicit drugs, with most samples containing the cutting agent in vast excess to the active component. This presents a significant analytical challenge, since diluents may be fluorescent or Raman active, so interference, suppression, or obscuration during regular Raman analysis can occur [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Colombo Plan scientists partnered with NMS Labs (Horsham, PA) to test street drug samples of opioid and cocaine from Vermont and Kentucky to determine whether adulterants similar to those found overseas were also appearing in the United States. 20 Using quadrupole time-of-flight mass spectrometry, a technology not routinely found in forensic or clinical laboratories, they identified multiple additional pharmacologically active components in most of the drug samples. A total of 301 of 311 (97%) samples collected in Vermont and 107 of 120 (89%) samples collected in Kentucky contained multiple additional pharmacologically active components (Figure).…”
Section: Emerging Us Trends In the Role Of Adulterantsmentioning
confidence: 99%
“…Number of pharmacologically active components identified in street drug samples from Vermont (n ¼ 311) and Kentucky (n ¼ 120), 2017 20. Illicitly manufactured drugs commonly contain additional pharmacologically active components that are added during the manufacturing process, some of which are known as adulterants or cutting agents.…”
mentioning
confidence: 99%
“…In a more recent analysis of heroin (n = 325) and synthetic opioid (n = 156) seizures from Kentucky and Vermont, authors found slight variation in cutting agents across the two sets of drugs and that caffeine and quinine or quinidine were mostcommon adulterants. Seizures of synthetic opioids, such as fentanyl, reported greater frequency of adulteration with diphenhydramine, acetaminophen, benzocaine, xylazine, and diltiazem (Fiorentin et al, 2018). We reproduce the relevant sections of their analysis in Table 5.3.…”
Section: Resultsmentioning
confidence: 99%